The Performance of Value and Growth Portfolios in East Asia before the Asian Financial Crisis - DING, David K. (Institutional Knowledge at Singapore Management University, 2005)
We examine value and growth portfolios in seven East Asian countries just before the onslaught of the 1997 Asian Financial Crisis. The value premiums in these countries, except in Indonesia, Taiwan, and Thailand, are found to be mainly positive. After controlling for firm size, risk, liquidity, and growth potential, we find higher returns among value stocks with a small firm size and low growth potential in Hong Kong and Malaysia. In Japan and Singapore, higher returns are found in growth portfolios with a small firm size and low growth potential. Growth stocks in Taiwan with a small firm size, and those in Thailand with a large firm size, have higher returns.